ACTR-59. A PHASE 1 STUDY OF BPM31510 PLUS VITAMIN K IN SUBJECTS WITH HIGH-GRADE GLIOMA THAT HAS RECURRED ON A BEVACIZUMAB-CONTAINING REGIMEN. (11th November 2019) - Recht, Lawrence; Thomas, Reena; Bertrand, Sophie; Yerballa, Priya; Li, Gordon; Iv, Michael; Narain, Niven; Sarangarajan, Rangaprasad; Granger, Elder; Nagpal, Seema
Abstract: BACKGROUND: High-grade gliomas (HGG) are characterized by dysregulated metabolism, utilizing glycolysis for energy production to support unrestricted growth. BPM 31510, an ubidecarenone (coenzyme Q10) containing lipid nanodispersion, causes a switch in cancer energy sourcing from glycolysis towards mitochondrial oxidative phosphorylation in vitro, reversing the Warburg effect and suggesting potential as an anti-tumor agent. The current study is a phase I study of BPM31510 + vitamin K in GB with tumor growth after bevacizumab (BEV). METHODS: This is an open-label phase I study of BPM31510 continuous infusion with weekly vitamin K (10mg IM) in HGG patients using an mTPI design, starting at 110mg/kg, allowing for a single dose de-escalation and 2 dose-escalations. Patients had received first-line ChemoRadiation and were in recurrence following a BEV containing regimen. RESULTS: 9 eligible and evaluable patients completed the 28 day DLT period. 8 patients had primary GB, 1 had anaplastic astrocytoma with confirmed pathologic transformation to GB. Median age was 55 years (27–67) and median KPS 70 (60–90) at enrollment. 4 patients were treated at the highest dose 171mg/kg, where there was a single DLT: Grade 3 AST & ALT. The most common grade 1–2 AEs possibly, probably or definitely related to drug were elevated AST, rash, and fatigue, each occurring in 3 patients. Median OS for 9 eligible/evaluable patients was 128 days (95% CI: 48–209) while PFS was 34 days (CI of mean 8.9). 3 patients are currently alive; 2 patients have survived >1 year. PK/PD data are being processed and will be presented. CONCLUSION: This study confirms that BPM 31510 + vitamin K is safe and feasible in treatment-refractory HGG patients. Though this study demonstrates safety at 171mg/kg, the proposed dose for future studies in GB, based on additional pre-clinical and non-GB clinical data is 88mg/kg.